Dynamic response of a damaged masonry rail viaduct: Measurement and interpretation. (1st August 2018) - Acikgoz, Sinan; DeJong, Matthew J.​; Kechavarzi, Cedric; Soga, Kenichi
Highlights: A damaged masonry viaduct was monitored with quasi-distributed sensing techniques. Strain and displacement response of two adjacent spans were measured. Results demonstrate pier movements in the longitudinal and transverse directions. 3D arch response, influenced by pier rotations and existing damage, is illustrated. Response to different loads and structural deterioration over time are examined. Abstract: Despite recent advances in modelling and testing techniques, assessing the serviceability of ageing masonry rail bridges remains a significant challenge. Most assessment methods are based on ultimate strength, while reliable measurement-based assessment criteria are lacking. This paper aims to improve the understanding of serviceability behaviour through detailed dynamic monitoring of the bridge locally (e.g. in locations of damage) and globally (e.g. interaction of different components). Quasi distributed sensing techniques (Fibre Bragg Grating cables and Digital Image Correlation) were used to quantify the bridge dynamic response through extensive measurement of strains and displacements. Specifically, these techniques were applied to two damaged spans of the Marsh Lane viaduct in Leeds, UK. A detailed investigation of the dynamic pier and arch barrel movements reveal how the response mechanisms relate to, and likely propagate, the existing damage. For instance, rotation of piers in the bridge longitudinal plane causes significant span opening and closing, which in turn causes the skewbacks and backing to rock on the piers. This is accompanied by flexural deformation of the arch, which forces the existing transverse cracks to experience high compressive strains. Similarly, the transverse rotation of piers due to the presence of the relieving arches causes spreading of the relieving arches and opening of the longitudinal crack above. These observations provide new insight into behaviour and lead to suggestions for improving assessment techniques for masonry viaducts.